Gambaran Pelayanan Antenatal pada Masa Pandemi COVID-19 di Indonesia 2020-2021 - Anggraini Lolitasari; Hermie M. M. Tendean; Erna Suparman (e-CliniC, 2023)
Abstract: Antenatal care (ANC) is an essential examination during pregnancy to monitor the health of mothers and babies and is one of the efforts to reduce MMR and IMR. However, with the COVID-19 pandemic being declared a national disaster in Indonesia in 2020, there were restrictions on health services including antenatal care. To ensure that ANC continues to run well, guidelines have been created that regulate the implementation of ANC during the COVID-19 pandemic in Indonesia, which are important to comply with. This study aims to describe antenatal care during the COVID-19 pandemic in Indonesia in 2020-2021. The research method used is literature review. The results of the study show that in 2020-2021 most health facilities in Indonesia have carried out antenatal care according to the guidelines, by making appointments and screening for COVID-19 before antenatal care, health workers using PPE according to the guidelines, requiring implementation of health protocols, conducting ANC according to standards, ask pregnant women to study the MCH handbook, carry out classes for pregnant women according to guidelines, and run a planned referral system. Factors affecting antenatal care during the COVID-19 pandemic were human resources, facilities and infrastructure, sources of funds, changes in policies and SOPs, adherence of health workers to using PPE, fear of pregnant women, knowledge and attitudes of pregnant women, and adherence of pregnant women to implementing health protocols. Keywords: antenatal care; antenatal care guidelines; COVID-19 pandemic   Abstrak: Antenatal care (ANC) adalah pemeriksaan esensial pada masa kehamilan untuk memantau kesehatan ibu dan bayi dan merupakan salah satu upaya untuk menurunkan AKI dan AKB. Namun, dengan adanya pandemi COVID-19 yang ditetapkan sebagai bencana nasional di Indonesia pada tahun 2020, terjadi pembatasan pelayanan kesehatan termasuk pemeriksaan antenatal. Untuk menjamin ANC tetap berjalan dengan baik, dibuat pedoman yang mengatur pelaksanaan ANC selama masa pandemi COVID-19 di Indonesia, yang penting untuk dipatuhi. Penelitian ini bertujuan untuk mengetahui gambaran pelayanan antenatal pada masa pandemi COVID-19 di Indonesia pada tahun 2020-2021. Metode penelitian yang digunakan adalah literature review. Hasil penelitian menunjukkan pada tahun 2020-2021 sebagian besar fasilitas kesehatan di Indonesia telah melakukan pelayanan antenatal sesuai dengan pedoman, dengan melakukan pembuatan janji temu dan skrining COVID-19 sebelum pemeriksaan antenatal, petugas kesehatan menggunakan APD sesuai pedoman, mewajibkan penerapan protokol kesehatan, melakukan ANC sesuai standar, meminta ibu hamil mempelajari buku KIA, melaksanakan kelas ibu hamil sesuai pedoman, dan menjalankan sistem rujukan terencana. Faktor-faktor yang mempengaruhi pelayanan antenatal pada masa pandemi COVID-19 adalah SDM, sarana dan prasarana, sumber dana, perubahan kebijakan dan SOP, kepatuhan tenaga kesehatan menggunakan APD, rasa takut ibu hamil, pengetahuan dan sikap ibu hamil, dan kepatuhan ibu hamil menerapkan protokol kesehatan. Kata kunci: pelayanan antenatal; pedoman antenatal care; pandemi COVID-19